OWNERSHIP STRUCTURE AND CORPORATE GOVERNANCE - Rita Yuniarti,; Rahmat Taufik,; Muhammad Irvan Rachmat, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purposes of the research is to study and to analyze the effect of ownership structure on corporate governance, methods used in this research are explanatory. The unit of analysis is all banking companies listed on the Indonesia Stock Exchange period 2011 to 2018. Data is time series and in the form of financial data and quantitative data. This study uses the entire population of banking companies listed on the Indonesia Stock Exchange period 2011 to 2018.